Implementation of Canva Media in Learning Negotiation Texts for Class X of SMK Negeri 2 Semarang - Adianto, Irham Husna; Asropah; Sri Wahyuni; Ngatmini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the implementation of Canva learning media in class 10 negotiation text learning materials at SMK Negeri 2 Semarang. Negotiation text is an important material in Indonesian that requires communication skills and creativity. However, conventional learning often makes students feel less motivated and find it difficult to understand the concept of negotiation texts. Therefore, this research explores the use of Canva media as an interesting and creative learning tool. The research method used is a qualitative approach with data collection techniques through observation, interviews and documentation. Participants in this research were Indonesian language teachers and class X students at SMK Negeri 2 Semarang. The data obtained was analyzed descriptively to determine the impact of using Canva media on students' learning motivation, creativity and understanding of the concept of negotiation texts. The research results show that the implementation of Canva media in learning negotiated texts has a positive impact on students' learning motivation and creativity. Apart from that, using Canva media also helps students understand the concept of negotiation text.